Browning of White Fat: Novel Insight Into Factors, Mechanisms, and Therapeutics. Issue 1 (21st June 2016) - Jeremic, Nevena; Chaturvedi, Pankaj; Tyagi, Suresh C.
Abstract : What is more interesting about brown adipose tissue (BAT) is its ability to provide thermogenesis, protection against obesity by clearing triglycerides, releasing batokines, and mitigating insulin resistance. White adipose tissue (WAT) on the other hand stores excess energy and secretes some endocrine factors like leptin for regulating satiety. For the last decade there has been an increasing interest in the browning of fat keeping in view its beneficial effects on metabolic disorders and protection in the form of perivascular fat. Obesity is one such metabolic disorder that leads to significant morbidity and mortality from obesity‐related disorders such as type 2 diabetes mellitus (T2D) and cardiovascular disease risk. Browning of white fat paves the way to restrict obesity and obesity related disorders. Although exercise has been the most common factor for fat browning; however, there are other factors that involve: (1) beta aminoisobutyric acid (BAIBA); (2) gamma amino butyric acid (GABA); (3) PPARɣ agonists; (4) JAK inhibition; and (5) IRISIN. In this review, we propose two novel factors musclin and TFAM for fat browning. Musclin a myokine released from muscles during exercise activates PPARɣ which induces browning of WAT that has beneficial metabolic and cardiac effects. TFAM is a transcription factor that induces mitochondrial biogenesis. Since BAT is rich in mitochondria, higher expression of TFAM in WAT or TFAM treatment in WAT cells can induce browning of WAT. We propose that fat browning can be used as a therapeutic tool for metabolic disorders and cardiovascular diseases. J. Cell. Physiol. 232: 61–68, 2017. © 2016 Wiley Periodicals, Inc. Abstract : What is more interesting about brown adipose tissue (BAT) is its ability to provide thermogenesis, protection against obesity by clearing triglycerides, and mitigating insulin resistance. This review describes the important therapeutic aspects of fat browning through factors like GABA, BAIBA, PPARϒ, IRISIN, musclin, and TFAM.